New Decisions on Patent Law - Heath, Christopher (Zeitschrift für Japanisches Recht, 2015)
Patent Act sec. 100, Civil Code sec. 1 par. 3 – “Samsung v. Apple – Standard patent and abuse of rights” A patent proprietor who has made a FRAND declaration for standard patent, is estopped from claiming injunctive relief based on the infringement of the standard patent against a third party that complies with the FRAND terms and has been willing to obtain a license. Intellectual Property High Court, decision of 16 May 2014 Samsung v. Apple Patent Act sec. 102 – “Apple v. Samsung – Standard patents and damage claim” Once a patentee has agreed that its patent is used for a standard on FRAND terms, damages against third parties can only be claimed in the amount of a licensing fee according to FRAND terms. This does not apply where the third party has not made efforts to obtain a license on FRAND terms. Intellectual Property High Court, decision of 16 May 2014 Apple v. Samsung